Sistemas de manejo e sucessão de culturas na qualidade do solo nos tabuleiros costeiros sergipano - Resende, Sérgio Carlos (2009)
The region of the Table Lands Sergipano is characterized by intense intemperization, because the influence of the high regime of rainfall and conditions of high temperature, so that there are mainly changes in physical and chemical properties of soil. The search for productive and environmental sustainability in agroecosystems is necessary to measure indicators of soil quality, to determine the behavior of physical attributes, chemical and microbiological for them to develop a management systems that degrade less the environment without compromising the productivity. This work have for aim evaluate the quality soil, through indicators of quality in different management systems (no-tillage, minimum tillage and conventional tillage), using leguminous plants (plants coverage: Pea (Cajanus cajan) and Sunn hemp (Crotalaria juncea); plants commercial: Bean (Phaseolus vulgares) and Peanut (Arachis hypogea)) in succession to the cultivation of sweet corn in agroecosystem of a soil classified as Ultissol Red Yellow located on the Campus Rural of the University Federal of Sergipe. The agronomics parameters were assessed: physical (mechanical resistance to penetration, density, diameter average weighted and percentage of aggregates stable in water), chemical (cation exchange capacity, base saturation and content of phosphorus) and microbiological (microbial biomass, breath basal and ratio of breath). The system notillage went who more contributed for improve the quality of soil proportianing better conditions physical, chemical and microbiological to the soil as: lower value of resistance to penetration from the depth of 20 cm, higher value of diameter average weighted, higher percentage of aggregates stable in water, higher value of CTC (cation exchange capacity), higher value of V (base saturation), higher value on the content of phosphorus, higher microbial biomass, lower value of breath basal, lower value of ratio of breath, higher value of total organic carbon. On the cultures tested in succession there was a large variation in results, with the plots where the sun hemp (Crotalaria juncea) was grown, it was obtained lower mechanical resistance to penetration at all depths no system no-tillage. In plots where it was grown pea (Cajanus cajan) were obtained highest values of phosphorus in the system no-tillage. The highest yield of sweet corn (Zea mays L.) was obtained in the system of cultivation no-tillage in respect minimum tillage and conventional tillage, and the sunn hemp provided greater productivity of sweet corn (Zea mays L.) in minimum tillage systems and conventional. The bean (Phaseolus vulgares) provided the greatest productivity of sweet corn (Zea mays L.) cultivation system no-tillage.